ANALYSIS OF KNOWLEDGE OF PHYSICS EDUCATION STUDENTS ABOUT SOLAR CELL UTILIZATION TECHNOLOGY - Rahayu, Ani Puji; Sundarti, Sundarti (EduFisika: Jurnal Pendidikan Fisika, 2021)
The purpose of this study was to determine the knowledge in critical thinking of physics education students about the use of solar cell technology. This study uses a qualitative approach. The subjects in this study were 40 students of physics education at the University of Jember. Critical thinking indicators that must be studied are analysis, explanation, interpretation, evaluation, inference, and self-regulation. The research instrument used a test given via google form. The results showed that the percentage of students who were able to answer questions correctly was still relatively low. This shows that the knowledge of physics education students at the University of Jember about solar cell energy is still very lacking.